Accuracy of references in a journal article - N Shah, Jay; Shah, Jenifei; Gupta, Abhishek; P Joshi, Naresh; Malla, Ashesh; Shah, Sanjeeb (Journal of Chitwan Medical College, 2025)
References and citations provide a scientific basis for verifying evidence. They facilitate further reading, research and the validation of new information. The accuracy of references and citations, along with functional hyperlinks to their sources, is crucial for maintaining the integrity and credibility of academic work. Proper citation and referencing contribute to the reproducibility of research, which is essential for verifying findings, upholding academic integrity, and ensuring accountability for the information and statements provided by the author. This is fundamental to good scientific practice. Accurate referencing helps legitimize scientific evidence, enhances the credibility of authors, journals, and editors, and adds value to the overall quality of academic work